ANALISIS KERJASAMA GURU PAI DAN ORANGTUA DALAM MEMBINA AKHLAK SISWA DI SD NEGERI 46 SELUMA - Mardiansyah Mardiansyah; Ifnaldi Ifnaldi; Sutarto Sutarto; Siswanto Siswanto (Al-Mau'izhoh, 2023)
This research is motivated by the behavior and habits that often occur in the classroom or outside the classroom showing unfavorable behavior such as fighting with friends, being impolite and obedient to the teacher, fighting, bullying fellow friends, urinating in class, carrying lipstick and makeup, skipping class when class hours, stealing the teacher's motorbike, and smoking in the school environment. This study aims to determine the moral condition of students at SD Negeri 46 Seluma and the form of cooperation between PAI teachers and parents in fostering students' morals at SD Negeri 46 Seluma. This study used qualitative research methods. The informants of this research were principals, PAI teachers, classroom teachers, parents and students. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusions/verification. good morals such as fellow students are still found fighting among friends and bullying fellow friends, students' morals towards teachers and parents are still lacking in respect and obedience, students' morals with the environment also have not shown maintaining the cleanliness of the school environment and home environment. The form of cooperation between PAI teachers and parents in fostering student morals at SD Negeri 46 Seluma is to invite parents to school and make direct visits to students' parents' homes. Analysis of the cooperation between PAI teachers and parents in fostering the morals of students at SD Negeri 46 Seluma with the collaboration of inviting parents to school and making direct visits to the students' parents' homes as for the changes obtained by students, namely not repeating, such as not fighting with fellow friends and not bullying others his friend again, the teacher is polite and doesn't pee carelessly anymore